Enhanced spontaneous activity of the mu opioid receptor by cysteine mutations: characterization of a tool for inverse agonist screening. - Brillet, Karl (BioMed Central, 2003)
BACKGROUND: The concept of spontaneous- or constitutive-activity has become widely accepted and verified for numerous G protein-coupled receptors and this ligand-independent activity is also acknowledged to play a role in some pathologies. Constitutive activity has been reported for the mu opioid receptor. In some cases the increase in receptor basal activity was induced by chronic morphine administration suggesting that constitutive activity may contribute to the development of drug tolerance and dependence. Constitutively active mutants represent excellent tools for gathering information about the mechanisms of receptor activation and the possible physiological relevance of spontaneous receptor activity. The high basal level of activity of these mutants also allows for easier identification of inverse agonists, defined as ligands able to suppress spontaneous receptor activity, and leads to a better comprehension of their modulatory effects as well as possible in vivo use. RESULTS: Cysteines 348 and 353 of the human mu opioid receptor (hMOR) were mutated into alanines and Ala(348,353 )hMOR was stably expressed in HEK 293 cells. [(35)S] GTPγS binding experiments revealed that Ala(348,353 )hMOR basal activity was significantly higher when compared to hMOR, suggesting that the mutant receptor is constitutively active. [(35)S] GTPγS binding was decreased by cyprodime or CTOP indicating that both ligands have inverse agonist properties. All tested agonists exhibited binding affinities higher for Ala(348,353 )hMOR than for hMOR, with the exception of endogenous opioid peptides. Antagonist affinity remained virtually unchanged except for CTOP and cyprodime that bound the double mutant with higher affinities. The agonists DAMGO and morphine showed enhanced potency for the Ala(348,353 )hMOR receptor in [(35)S] GTPγS experiments. Finally, pretreatment with the antagonists naloxone, cyprodime or CTOP significantly increased Ala(348,353 )hMOR expression. CONCLUSION: Taken together our data indicate that the double C348/353A mutation results in a constitutively active conformation of hMOR that is still activated by agonists. This is the first report of a stable CAM of hMOR with the potential to screen for inverse agonists.